Comparing trade-off adjustments in credit risk analysis of mortgage loans using AHP, Delphi and MACBETH - Ferreira, F. A. F.; Santos, S. P. (International Journal of Strategic Property Management, 2016)
Due to the severe restrictions on access to credit resulting from the current economic climate, credit risk analysis of mortgage loans has been considered paramount for banking institutions and is currently accompanied by higher credit underwriting standards. In this paper, we present an empirical comparison of three decision support tools (i.e. Analytic Hierarchy Process (AHP), Delphi, and Measuring Attractiveness by a Categorical Based Evaluation Technique (MACBETH)) in the specific context of trade-off readjustments in credit risk analysis of mortgage loans. We conducted a panel study with credit analysts and focused on five lines of comparison: ease of use; time-consumption; ease of applicability; accuracy; and overall evaluation. Results indicate that Delphi surpasses AHP and MACBETH in terms of ease of use, time-consumption and ease of applicability. As for accuracy, the differences obtained between AHP and MACBETH are not significant, and both methods perform better than Delphi. Most of the decision makers considered AHP the "overall best" approach.